Effects of rosmarinus offi cinalis essential oil on germ tube formation by candida albicans isolated from denture wearers - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2013)
The aim of this study was to investigate the effects of Rosmarinus offi cinalis essential oil on germ tube formation by Candida albicans isolated from denture wearers. Methods: Ten C. albicans isolates recovered from denture wearers were tested using 10% fetal bovine serum with or without 4% R. offi cinalis essential oil. Results: The essential oil from R. offi cinalis completely inhibited germ tube formation in the investigated C. albicans isolates. Conclusions: The results demonstrate that the essential oil of R. offi cinalis modulates C. albicans pathogenicity through its primary virulence factor (i.e., germ tube formation was suppressed).
Efeitos do óleo essencial de rosmarinus officinalis na formação de tubo germinativo por candida albicans isoladas de usuários de próteses dentárias
Keywords: Candida albicans; Germ Tube; Rosmarinus offi cinalis; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA